Microarray Expression Profiling and Raman Spectroscopy Reveal Anti-Fatty Liver Action of Berberine in a Diet-Induced Larval Zebrafish Model - Bo Chen; Bo Chen; Yang-Min Zheng; Yang-Min Zheng; Yang-Min Zheng; Miao-Qing Zhang; Miao-Qing Zhang; Miao-Qing Zhang; Miao-Qing Zhang; Ying Han; Jing-Pu Zhang; Jing-Pu Zhang; et al. (Frontiers Media S.A., 2020)
Background: The prevalence of non-alcohol fatty liver disease (NAFLD) is increasing in children and adolescents who are mostly resulted from overfeeding. Previous studies demonstrate that berberine (BBR), a compound derived from plant, has beneficial effects on NAFLD in adults but poorly understood in the pediatric population. This study employed a larval zebrafish model to mimic the therapeutic effects of BBR in the pediatric population and the mechanisms underlying its hepatoprotection.Methods: High-cholesterol diet (HCD)-fed zebrafish exposed to BBR at doses of 0, 1, 5, and 25 μM. After the larvae were treated with BBR for 10 days, its effect on hepatic steatosis was evaluated. We introduced Raman imaging and three-dimensional (3D) molecular imaging to detect changes in the biochemical composition and reactive oxygen species (ROS) levels of zebrafish liver. Gene expression microarray was performed to identify differentially expressed genes (DEGs) followed by gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and functional category analysis.Results: BBR (5 and 25 μM) administration prevented HCD-induced liver lipid accumulation in larval zebrafish. The result was further confirmed by the pathological observation. Raman mapping indicated that the biochemical composition in the liver of BBR-treated group shifted to the control. The quantitative analysis of 3D imaging showed that the ROS level was significantly decreased in the liver of BBR-treated larvae. In the livers of the BBR group, we found 468 DEGs, including 172 genes with upregulated expression and 296 genes with downregulated expression. Besides, GO enrichment, KEGG pathway, and functional category analysis showed that various processes related to glucolipid metabolism, immune response, DNA damage and repair, and iron were significantly enriched with DEGs. The expression levels of the crucial genes from the functional analysis were also confirmed by quantitative PCR (qPCR).Conclusion: BBR can significantly improve hepatic steatosis in HCD-fed zebrafish larvae. Its mechanisms might be associated with the regulation of lipid metabolism, oxidative stress, and iron homeostasis. Raman imaging in larval zebrafish might become a useful tool for drug evaluation. Mainly, the gene expression profiles provide molecular information for BBR on the prevention and treatment of pediatric NAFLD.